Forensic accounting: Perpetrators of fraud / Hari Ramulu Munusamy - Munusamy, Hari Ramulu (2006)
Fraud can be perpetrated by an individual, two or more individuals, or by many groups or 'separate entities'. Most fraud cases are not reported due to risk of embarrassment and resulting reduction in the level of customer or shareholder confidence. Reported fraud cases (a majority of the worst kind) are committed by a company's own employees or managers.